The inclusion of children with special educational needs in an Intensive French as a Second-Language program: From theory to practice - Joy, Rhonda; Murphy, Elizabeth (Canadian Journal of Education/Revue canadienne de l’éducation, 2012)
This paper portrays the activity system of eight classes of Grade 6 children with special educational needs in an Intensive French as a second-language education program. Classroom norms and tools reflected a social-interactionist and social-constructivist approach with scaffolding, social interaction, multiple modes of representing, holistic, cross-curricular, child-centred, active, and meaningful learning. Outcomes of the activity system of the children included basic French communication ability, positive behaviour changes, heightened selfesteem, increased motivation, participation, and engagement. We conclude with implications related to the feasibility, scalability, and sustainability of practices for non-Intensive French classrooms. Keywords: Special educational, elementary school, Intensive French, inclusion, Activity theory, social-constructivism